Efektivitas Ekstrak Tumbuhan untuk Mengeliminasi Clavibacter michiganensis subsp. michiganensis pada Benih Tomat - Aprizal Zainal; Aswaldi Anwar; Satriyas Ilyas; , Sudarsono; , Giyanto (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2010)
Objectives of experiments were to evaluate (1) in vitro inhibitory effects of plant extracts on Clavibacter michiganensis subsp. michiganensis (Cmm), (2) inhibitory effects of plant extracts on Cmm infected tomato seeds, and (3) effectiveness of seed treatment plus plant extracts to eliminate Cmm. After evaluating 20 plant extracts, curcuma rhizome and betel vine leaf extract, cinnamon and clove oil were selected for further test. Tomato seeds were artificially inoculated with Cmm to obtain high level of infection. Part of the seeds were dipped in either suspension of selected extracts for 20 minutes and the others were matriconditioned using a mixture of burned rice hull (at 22 °C and RH 60-70%) plus either of plant extracts oils, respectively. Elimination of Cmm level from infected seeds was observed at 10 days after treatments. Results of the experiment indicated curcuma extract, betel vine extract, cinnamon oil or clove oil showed in vitro inhibitory effects on Cmm. Moreover, dipping infected seeds in either 5% of curcuma, betel vine extract, or 0.5% of clove oil or matriconditioning plus these extracts oils were effective to eliminate Cmm from infected seeds. These treatments may potentially be used and developed commercially for eliminating seedborne Cmm on infected tomato seeds.   Keywords: Bacterial cancer, seedborne-pathogen, seed-treatments